Frontispiece: Bottom‐up Construction of π‐Extended Arenes by a Palladium‐Catalyzed Annulative Dimerization of o‐Iodobiaryl Compounds. Issue 29 (11th July 2018) - Zhu, Chendan; Wang, Di; Wang, Dingyi; Zhao, Yue; Sun, Wei‐Yin; Shi, Zhuangzhi
Abstract : Annulation . In their Communication onpage 8848 ff., Z. Shi et al. report palladium‐catalyzed annulative dimerization of o ‐iodobiaryl species. Aromatic compounds with triphenylene cores are generated, including small graphene nanoribbons.